NANOTECHNOLOGY IN ENVIRONMENTAL REMEDIATION: A SUSTAINABLE FRONTIER (Journal of Medical & Health Sciences Review, 2025)
With traditional remediation methods frequently proving insufficient, expensive, and environmentally intrusive, environmental pollution has become a major worldwide concern. Nanotechnology has emerged as a viable substitute for environmental remediation in recent years, providing long-lasting and incredibly effective solutions. This study investigates the use of nanotechnology to combat pollution in the air, water, and soil. Nanomaterials like metal oxides, carbon-based structures, and biogenic nanoparticles can efficiently remove or neutralize a variety of contaminants because of their special physicochemical characteristics, which include a high surface area-to-volume ratio, enhanced reactivity, and tunable surface functionalities. The study provides a thorough examination of the processes that nanomaterials use to function, such as photocatalysis, redox reactions, and adsorption. The importance of biocompatible and green-synthesized nanoparticles as environmentally friendly choices that support sustainability and a smaller environmental impact is emphasized. The study also includes case studies, real-world applications, and a comparison of the efficiencies of conventional and nanotech-driven approaches. Concerns about the hazards that nanomaterials pose to the environment and human health, especially in relation to toxicity, long-term ecological effects, and regulatory gaps, remain despite their potential. In order to ensure safe implementation, the paper discusses these issues and promotes thorough risk assessments and policy frameworks. In the end, incorporating nanotechnology into environmental remediation offers a revolutionary strategy for creating cleaner ecosystems. Nanoremediation is a sustainable frontier that has the potential to greatly advance international environmental protection efforts with continued innovation and interdisciplinary cooperation.